Ear health and hearing surveillance in girls and women with Turner's syndrome: recommendations from the Turner's Syndrome Support Society. (28th September 2016) - Kubba, H.; Smyth, A.; Wong, S.C.; Mason, A.
Abstract : Background: Turner's syndrome (TS) is a common chromosomal disorder, affecting one in 2000 newborn girls, in which part or all of one X chromosome is missing. Ear and hearing problems are very common in girls and women with TS. The aim of this review was to review the published literature to suggest recommendations for otological health surveillance. Method: A keyword search of Ovid Medline was performed for published literature on the subject and evidence rated according to the GRADE criteria. Results: Middle ear disorders are very common and persistent in girls and women with TS as are progressive sensorineural hearing loss and balance disorders. Conclusions: Otolaryngologists should be aware of the high prevalence and challenging nature of all forms of ear disease in individuals with TS. Early intervention may offer benefits to health and education, and we advocate routine lifelong annual hearing screening in this group.